LAMP Using a Disposable Pocket Warmer for Anthrax Detection, a Highly Mobile and Reliable Method for Anti-Bioterrorism - Hatano, Ben; Maki, Takayuki; Obara, Takeyuki; Fukumoto, Hitomi; Hagisawa, Kohsuke; Matsushita, Yoshitaro; Okutani, Akiko; Bazartseren, Boldbaatar; Inoue, Satoshi; Sata, Tetsutaro; Katano, Harutaka (Japanese Journal of Infectious Diseases, 2010)
A quick, reliable detection system is necessary to deal with bioterrorism. Loop-mediated isothermal amplification (LAMP) is a DNA amplification method that can amplify specific DNA fragments in isothermal conditions. We developed a new highly mobile and practical LAMP anthrax detection system that uses a disposable pocket warmer without the need for electricity (pocket-warmer LAMP). In our tests, the detection limit of the pocket-warmer LAMP was 1,000 copies of Bacillus anthracis pag and capB gene fragments per tube. The pocket-warmer LAMP also detected B. anthracis genes from DNA extracted from 0.1 volume of a B. anthracis colony. The lower detection limit of the pocket-warmer LAMP was not significantly different from that of a conventional LAMP using a heat block, and was not changed under cold (4ºC) or warm (37ºC) conditions in a Styrofoam box. The pocket-warmer LAMP could be useful against bioterrorism, and as a sensitive, reliable detection tool in areas with undependable electricity infrastructures.